The effects of chronic AC magnetic field on contraction and relaxation of isolated thoracic aorta rings of healthy and diabetic rats - Öcal,Isil (2004)
The aim of in this study was to determine the effect of chronic alternating current (AC) magnetic field on the contraction and relaxation parameters of isolated thoracic aorta rings in healthy and diabetic rats. Sixty rats (Wistar albino spp) weighing between 250-300 g were used. The rats were divided into four groups: 1-Control (C), 2- control + magnetic field (C+MA), 3- experimental diabetic (DIA), 4- experimental diabetic and magnetic field (DIA+MA). Magnetic fields of 5 mT intensity and 50 Hz frequency oriented in the north-south direction was applied to the C+MA and DIA+MA groups for 2 hours each day for one month, after which rats were killed by decapitation and the thoracic aorta dissected. This showed attenuated contraction responses to phenylephrine (PE) and elevated relaxation responses to acetylcholine (ACh) of the thoracic aorta rings of rats in the C+MA and DIA+MA groups compared to group C but no changes in the relaxation responses to sodium nitroprruside (SNP) of thoracic aorta rings relative to group C and DIA. The weights of rats in DIA+MA or C+MA groups compared to the DIA and C groups decreased.